Airway Epithelial Cells Differentially Adapt Their Iron Metabolism to Infection With Klebsiella pneumoniae and Escherichia coli In Vitro - Grubwieser, Philipp; Hoffmann, Alexander; Hilbe, Richard; Seifert, Markus; Sonnweber, Thomas; Böck, Nina; Theurl, Igor; Weiss, Günter; Nairz, Manfred (Frontiers in Cellular and Infection Microbiology, 2022)
Background Pneumonia is often elicited by bacteria and can be associated with a severe clinical course, respiratory failure and the need for mechanical ventilation. In the alveolus, type-2-alveolar-epithelial-cells (AECII) contribute to innate immune functions. We hypothesized that AECII actively adapt cellular iron homeostasis to restrict this essential nutrient from invading pathogens – a defense strategy termed ‘nutritional immunity’, hitherto mainly demonstrated for myeloid cells. Methods We established an in-vitro infection model using the human AECII-like cell line A549. We infected cells with Klebsiella pneumoniae (K. pneumoniae) and Escherichia coli (E. coli), two gram-negative bacteria with different modes of infection and frequent causes of hospital-acquired pneumonia. We followed the entry and intracellular growth of these gram-negative bacteria, and analyzed differential gene expression and protein levels of key inflammatory and iron metabolism molecules. Results Both, K. pneumoniae and E. coli are able to invade A549 cells, whereas only K. pneumoniae is capable of proliferating intracellularly. After peak bacterial burden, the number of intracellular pathogens declines, suggesting that epithelial cells initiate antimicrobial immune effector pathways to combat bacterial proliferation. The extracellular pathogen E. coli induces an iron retention phenotype in A549 cells, mainly characterized by the downregulation of the pivotal iron exporter ferroportin, the upregulation of the iron importer transferrin-receptor-1 and corresponding induction of the iron storage protein ferritin. In contrast, cells infected with the facultative intracellular bacterium K. pneumoniae exhibit an iron export phenotype indicated by ferroportin upregulation. This differential regulation of iron homeostasis and the pathogen-specific inflammatory reaction is likely mediated by oxidative stress. Conclusion AECII-derived A549 cells show pathogen-specific innate immune functions and adapt their iron handling in response to infection. The differential regulation of iron transporters depends on the preferential intra- or extracellular localization of the pathogen and likely aims at limiting bacterial iron availability.